Mal de Debarquement Syndrome: A Rare Entity—A Case Report and Review of the Literature - Veronica Nwagwu; Rakesh Patel; Jerome Okudo (Case Reports in Otolaryngology)
Mal de Debarquement Syndrome (MDS) is a rare, understudied, underdiagnosed, and self-limiting condition. Etiology and incidence are unknown. It is characterized by abnormal sensation of motion/balance reported after travel by air, land, and sea; being reexposed to motion/activity relieves it. Symptoms may last from minutes to years. Workup though required reveals no findings; it is a diagnosis of exclusion. While no efficacious treatment exists, amitriptyline and benzodiazepines as well as supportive therapy have proved to be useful. We have described a 40-year-old Caucasian female who presented for the evaluation of persistent rocking and swaying sensation after a ship cruise which lasted for one week. Patient was treated with benzodiazepines after extensive workup and is now stable. A high index of suspicion is required to make a diagnosis.